MOTIVATING STUDENTS TO PARTICIPATE IN PROFESSIONALLY ORIENTED EVENTS MANAGEMENT - T. A. Shulgina; N. A. Ketova; K. A. Kholodova; D. A. Severinov (Russian State Vocational Pedagogical University, 2018)
Introduction. Nowadays, increasing the motivation of future specialists' to mastering general and special professional competences is one of the acute issues of the higher education system. Despite a wide-spread popularity and a considerable amount of studies on the problem connected with motivation of training in higher education institution, researchers have not dealt with a mechanism of start of a motivational impulse of professional self-determination and professionalizing such as participation of students in extra-curricular activities and events of professionally oriented format. At the same time, students can find many skills demanded in the chosen profession and practical experience only on condition of their active participation in extra-curricular activities, which allow them to expand and deepen knowledge of the chosen profession received during the classroom activities; to solidify separate blocks of theoretical material in an informal situation.The aims of the research presented in the article are the following: to identify and study the process of motivation to participation in the organization of extra-curricular activities and events of professional orientation among students of different university courses; to disclose the potential of similar work for formation of additional research, organizational, communicatory and other skills and abilities necessary for becoming a valuable specialist. Methodology and research methods. Analytical review and generalization of psychological, pedagogical and methodical literature on the considered problem was conducted at the initial stage of work. The methodological research base involves: conceptual substantive and procedural approaches to studying the phenomenon of motivation; David McClelland's Human Motivation Theory; Participatory Management Theory; Active Training Theory. Interactive game technologies, anonymous questioning, methods of descriptive and variation statistics were applied at experimental and final (resultant) stages. Processing of the obtained data was conducted by means of the license version of spreadsheet program Microsoft Excel 2010, as well as the Biostatistics 4.03 program.Results and scientific novelty. The practicability of a non-traditional game format of extra-curricular activities as innovative way of development and support of motivation to improvement of personal vocational training among students is proved. General motives of students' participation in the organization and holding extra-curricular professionally oriented events were revealed on the example of development and realization of educational quest undertaken by students of Kursk State Medical University. It is proved that students' interest in novelty is the strongest incentive stimulus that motivates young people to take part in voluntary extra-curricular activities beyond the scope of the training program. However, it is found out that accents of motivation depend on the specific personal valuable and substantive tasks solved at each age stage. Results of questioning, as a whole, have proven to be consistent with the conclusions of other studies: first-year students are attracted by non-standard forms of education allowing them to get acquainted closer with the content of the acquired education and future profession; a thirst for new knowledge, a desire to participate in activities and apply previously acquired knowledge is observed in the next two years of students' preparation; a desire to share experience with younger colleagues and try out as an event organizer is natural for undergraduates. In addition, it is studied out that the motive to learn event planning at the university level and thereby designate a new stage of own personal development is also typical for 2-4th-year students.Practical significance. The present research results might be useful for teachers and specialists of different university subdivisions who are involved in extracurricular activities planning and management.